CHRONIC CONSTIPATION IN CHILDREN. AN UPDATE ON EVALUATION AND MANAGEMENT - Felicia Galos; Mihai Stoicescu; Mihai Munteanu; Gabriela Nastase; Malina Anghel; Mihaela Balgradean (Amaltea Medical Publishing House, 2015)
Constipation is a common problem in childhood, with a children prevalence varying between 0.7% and 29.6%. Constipation is encountered in all pediatric age groups, with variably severity and duration, from mild and short to severe and chronic forms, with faecal impact and encopresis. This article review the epidemiological, clinical and therapeutically aspects of children constipation, functional in the majority of cases.